Personality, Motivation, and EFL Speaking Performance: Evidence from an English Education Program - Rohima, Aziza; Pitaloka, Nova Lingga (International Journal of Education Research and Development, 2025)
Studies investigating how personality traits, motivation levels, and speaking performance interact are still limited, particularly in the context of Pre-service English teachers in South Sumatera. Thus, this study aims to discover whether extroverts or introverts, based on their motivation levels, exhibit better speaking performance. The population consisted of 336 pre-service English teachers at a state university in South Sumatera, and a sample size of 120 students was chosen using convenience sampling technique. This study employed a quantitative correlational design, with data collection using questionnaires of motivation and personality traits and a speaking performance test and these data were analyzed using descriptive and inferential statistics, i.e. Two-way ANOVA. The results revealed that highly motivated extroverts performed slightly better than their introverted counterparts, and so did low-motivated extroverts, but their differences were not statistically significant. Moreover, the correlation analysis (p = 0.640) and Two-way ANOVA results (p = 0.356 for Personality and p = 0.774 for Motivation) demonstrated no significant correlation between personality traits, motivation levels, and speaking performance. These findings suggest that other than personality and motivation alone, other predictors such as linguistic competence, anxiety, and classroom dynamics might have contribution to speaking proficiency.